Philippine kinship and social organizaiton from the perspective of historical linguistics - Gallego, Maria Kristina S. (Quezon City Ateneo de Manila University, 2015)
"Based on a reconstruction of Proto-Philippine kinship and social organization terminologies, this article characterizes early Philippine kinship as bilateral with possible quasi-lineages. These features support the reconstruction of the Proto-Malayo-Polynesian system made by George Peter Murdock (1949) rather than that of Robert Blust (1980). In terms of leadership, the early Philippine community is described as dualistic in nature, allowing achieved and ascribed or hereditary chiefdom-thus deviating from the ancestral concept of hereditary leadership in the Proto-Malayo-Polynesian system. Changes in the Philippine kinship system are traced to show innovations in nomenclature and behavior toward certain kin."
Keywords: Linguistics; Kinship; Cultural reconstruction; Social organization